Factors influencing referral among women attending post abortion care at tertiary hospitals in Northern Uganda - Jimmyy Opee; Gerald Obai; Maria K. Wolters; Samuel Obonyo Okot; Simple Ouma; Emmanuel Ochola; Felix Bongomin (Scientific Reports)
Abstract Referral is critical in the chain of managing women receiving post-abortion care (PAC). We assessed factors influencing referral among women receiving PAC at two tertiary hospitals in Northern Uganda. An embedded, mixed-methods study design was conducted from July to December 2023. Quantitative data were collected from 152 women of reproductive age (15–49 years) using structured questionnaires, while qualitative data were gathered through 20 in-depth interviews with women and healthcare providers. Logistic regression was applied for quantitative analysis, and thematic content analysis was used for qualitative data. Median age of all participants was 26 years (IQR: 21–32). Referrals accounted for 46 (30.3%). The odds of being referred was significantly higher among rural residence (adjusted Odds Ratio (aOR): 15.5; 95% Confidence Interval (CI) 4.44–53.83; p < 0.001) and those under 20 years of age (aOR: 2.8; 95% CI 1.02–7.56; p = 0.046). Qualitatively, limited PAC services at lower-level facilities, financial barriers to private care, and transport challenges were key drivers for referral. Therefore, strengthening PAC services at lower-level facilities could reduce referrals and improve care access. Major economic reforms are essential to achieving universal health coverage, including PAC services in northern Uganda.